Effects of the Topical Application of Lavandula Officinalis L. Essential Oil on Reducing the Severity of Eczema Symptoms: A Randomized Clinical Trial - Marzieh Rashidipour; Mojgan Zarei Venovel; Forouzan Ahmadpour*; Farzad Ebrahimzadeh; Hossein Matoorian Pour; Samaneh Hadavand; Asma Alekasir (Lorestan University of Medical Sciences, 2023)
Background and Aim: Lavandula Officinalis L. essential oil (L.O) has different effects such as anti-inflammatory and soothing effects on skin diseases. The aim of this study was to examine the the effect of L.O on the severity of eczema. Materials and Methods: This research was conducted as an open-label, randomized clinical trial. The patients who were enrolled to participate in the present study were randomly divided into five groups. In groups A, B, and C, 15 patients in each group received lavender essential oil cream at a dose of 3%, 5%, and 8%, respectively. In groups D and E, 15 patients in each group received 1% topical hydrocortisone and cream base, respectively. All the patients used the cream twice a day for 14 days. Baseline characteristics of the enrolled subjects and illness severity were recorded at the baseline and during the 7th as well as 14th days. Results: Generalized estimating equations (GEE) method showed that the interaction of the experimental group and time factor on the severity of eczema was significant (P = 0.011). Moreover, the relative chance of higher eczema severity in experimental groups was different, and it was a function of time. The relative chance of any increase in the severity of eczema in groups A, B, C compared with group E on the 7th day of treatment was reduced by about 9.7%, 34.7%, and 73.9%, respectivelyt; while on the 14th day of treatment, it decreased by about 79.2%, 82.4%, and 97.7%, respectively. The lavender oil significantly reduced the severity of eczema at the 7th and end of the 14th day (P ≤ 0.01). Conclusion: Lavender has dose-dependently beneficial effects on the treatment of eczema.